Utilizing big data to provide better health at lower cost. - Jones, Laney K.; Pulk, Rebecca; Gionfriddo, Michael R.; Evans, Michael A.; Parry, Dean (American Journal of Health-System Pharmacy, 2018)
Purpose. The efficient use of big data in order to provide better health at a lower cost is described. Summary. As data become more usable and accessible in healthcare, organizations need to be prepared to use this information to positively impact patient care. In order to be successful, organizations need teams with expertise in informatics and data management that can build new infrastructure and restructure existing infrastructure to support quality and process improvements in real time, such as creating discrete data fields that can be easily retrieved and used to analyze and monitor care delivery. Organizations should use data to monitor performance (e.g., process metrics) as well as the health of their populations (e.g., clinical parameters and health outcomes). Data can be used to prevent hospitalizations, combat opioid abuse and misuse, improve antimicrobial stewardship, and reduce pharmaceutical spending. These examples also serve to highlight lessons learned to better use data to improve health. For example, data can inform and create efficiencies in care and engage and communicate with stakeholders early and often, and collaboration is necessary to have complete data. To truly transform care so that it is delivered in a way that is sustainable, responsible, and patient-centered, health systems need to act on these opportunities, invest in big data, and routinely use big data in the delivery of care. Conclusion. Using data efficiently has the potential to improve the care of our patients and lower cost. Despite early successes, barriers to implementation remain including data acquisition, integration, and usability.